(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Groundwater quality monitoring is very important in cities and towns where there were poor solid waste management. In this study, the effects of solid waste on groundwater in Damaturu Metropolis along Potiskum road was investigated using both electrical resistivity survey and hydro-chemical methods. The results of the study showed that the solid waste at the dump sites generate leachate which percolate into the subsurface to pollute the groundwater. Two aquifers were delineated in the study area and the ERT survey results showed that the groundwater in the first aquifer was contaminated. The contaminants were characterized by very low resistivity which distinguished them from their host rocks. The contaminants are highly conductive which indicate that they were inorganic and possibly of metallic origin. The results of the analyzed water samples from the study area revealed that heavy metals such as Cadmium, Arsenic, Iron, Chromium, and Lead were in elevated concentration in the groundwater of the study area. The first aquifer in the study area is semi-confined and its proximity to the earth surface made it much vulnerably to pollution. The second aquifer is confined by a very thick sandy-clay formation which protects it from pollution by contaminant plumes. It is the most appropriate for groundwater abstraction in the study area. Considering the health hazards associated with the consumption of polluted groundwater, we therefore recommend that all the hand dug wells and shallow boreholes in the study area should be closed down for safety and the solid waste dump sites should be...